Evaluation of the Accuracy of Implementation of Obstetric Referral Cases to the Emergency in the JKN Era: Evaluasi Ketepatan Pelaksanaan Rujukan Kasus Gawat Darurat Obstetri ke Instalasi Gawat Darurat dalam Era Jaminan Kesehatan Nasional - Omo A. Madjid; Arietta R.D. Pusponegoro; Immanuel S. Margatan (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objective: To investigate the circumstances of the obstetric referral case at the emergency department of the Dr.Cipto Mangunkusumo Hospital as well as the accuracy of the referral implementation. Method: We used cross-sectional study. Medical records of obstetric patients at Emergency department in RSCM in January 2013-July 2014 were obtained, then information about patients and their characteristic were collected. The accuracy of referral cases is based on emergency obstetric criteria by BPJS rules. Results: Primary Health Care became the leading referrer. Inappropriate diagnostic referral cases amounted to 21.2%when JKN first began to be implemented in 2014. Cases with improper diagnoses were more referred when JKN was implemented which amounted to 16.8% and non-emergency referral cases of 6.9% in 2014. Conclusion: Referral implementation has not been efficient and effective, the number of obstetric referral cases to emergency department of RSCM that can actually be handled in the secondary advanced health services after the application of JKN is still high. Monitoring and evaluation is needed by the Local Health Office to improve the quality of the referral system that applied in the newly JKN era. Keywords:accuracy of referrals,BPJS, JKN, obstetric emergencies, referral system. Abstrak Tujuan: Mengetahui gambaran kasus rujukan obstetri di IGD RSCM dan ketepatan pelaksanaan rujukan. Metode: Deskriptif desain studi potong lintang. Data diambil dari rekam medis pasien obstetri di IGD RSCMpada bulan Januari 2013 hingga Desember 2014, kemudian informasi mengenai data dan karakteristik pasien dikumpulkan. Ketepatan pelaksanaan rujukan kasus gaat daraurat obstetri berdasarkan Krietria gawatdarurat bagian kebidanan menurut ketentuan BPJS Kesehatan. Hasil: Perujuk terbanyak adalah Puskesmas (FKTP). Kasus rujukan dengan ketidaksesuaian diagnosa lebih banyakjumlahnya pada saat JKN mulai diterapkan pada tahun 2014 sebesar 21.2%. Kasus dengan diagnosa yang tidak tepat rujuk lebih banyak pada saat JKN di laksanakan yaitu sebesar 16.8% dan kasus rujukan yang bukan gawatdarurat sebesar 6.9% pada tahun 2014. Kesimpulan: Pelaksanaan rujukan belum efisien dan efektif, jumlah rujukan obstetri ke IGD RSCM yangsebenarnya dapat ditangani di fasilitas kesehatan tingkat lanjutan sekunder setelah penerapan JKN masih tinggi. Dibutuhkan monitoring dan evaluasi oleh Dinas Kesehatan setempat untuk meningkatkan kualitas sistem rujukan yang berlaku di era JKN yang baru diterapkan. Kata kunci : BPJS, gawat darurat obstetri, JKN, ketepatan rujukan, sistem rujukan.